Genetic diversity and phylogenetic analyses of 11 cohorts of captive rhesus macaques from Chinese zoos - Su, Qian; Yao, Yongfang; Zhao, Qin; Li, Diyan; Xie, Meng; Wu, Jiayun; Wen, Anxiang; Wang, Qin; Zhu, Guangxiang; Ni, Qingyong; Zhang, Mingwang; Xu, Huailiang (PeerJ, 2019)
Rhesus macaques are raised in almost every Chinese zoo due to their likeability and ease in feeding; however, little is yet known about the genetic diversity of rhesus macaques in captivity. In this study, a 475-base pair nucleotide sequence of the mitochondrial DNA control region was obtained from the fecal DNA of 210 rhesus macaque individuals in captivity. A total of 69 haplotypes were defined, 51 of which (73.9%) were newly identified. Of all haplotypes, seven were shared between two zoos, and 62 haplotypes (89.8%) appeared only in a specific zoo, indicating a low rate of animal exchange between Chinese zoos. Moreover, there was a relatively high level of genetic diversity among the rhesus macaques (Hd = 0.0623 ± 0.0009, Pi = 0.979 ± 0.003, K = 28.974). Phylogenetic analysis demonstrated that all haplotypes were clearly clustered into two major haplogroups—Clade A (southeastern China) and Clade B (southwestern China)—and each major clade contained several small sub-haplogroups. The haplotypes of rhesus macaques from the same zoo were not clustered together for the most part, but scattered among several subclades on the phylogenetic tree. This indicates that the rhesus macaques in most Chinese zoos may originat from a diverse collection of geographical areas. Our results demonstrate that zoos play an important role in the conservation of the genetic diversity of rhesus macaques, as well as provide useful information on the genetic management of captive rhesus macaques.
Keywords: Mitochondrial DNA; Rhesus macaque; Macaca mulatta; Genetic diversity; Phylogenetic analysis